(untitled) (TEL Tempo, Espaço e Linguagem, 2026)
Abstract: The article historically analyzes policies for the protection of childhoods and youth in Brazil, from the 1988 Constitution to the Digital Statute of the Child and Adolescent. By articulating childhood historiography with Foucauldian notions of biopolitics and governmentality, it interprets integral protection as a rationality of governing life, oriented toward prevention, monitoring, and the anticipatory management of social and digital risks. Keywords: Childhoods; Youth; Integral protection; Biopolitics; Governmentality.